Local Zinc Chloride Release From a Calcium Sulfate Carrier Enhances Fracture Healing. Issue 3 (March 2017) - Krell, Ethan S.; Ippolito, Joseph A.; Montemurro, Nicholas J.; Lim, Phillip H.; Vincent, Richard A.; Hreha, Jeremy; Cottrell, Jessica; Sudah, Suleiman Y.; Muñoz, Maximilian F.; Pacific, Kristen P.; Benevenia, Joseph; O'Connor, J. Patrick; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: This study examined the efficacy of calcium sulfate (CaSO4 ) as a carrier for intramedullary delivery of zinc chloride (ZnCl2 ) to treat fracture healing in a BB Wistar rat model. A non–carrier-mediated injection of 3.0 mg/kg of ZnCl2 has previously been shown to enhance fracture healing. Methods: A heterogeneous mixture of ZnCl2 and CaSO4 was administered into the intramedullary femoral canal and a mid-diaphyseal femur fracture was created unilaterally. Early and late parameters of fracture healing were assessed using biomechanical testing, radiographic scoring, quantitative histomorphometry (for percentage of new cartilage and bone within the fracture callus), and long-term histologic evaluation. Results: Fractures treated with 1.0 mg/kg of ZnCl2 /CaSO4 demonstrated a significantly higher maximum torque to failure compared with both CaSO4 ( P = 0.048) and saline ( P = 0.005) controls at 4 weeks postfracture (396.4 versus 251.3 versus 178.7 N mm, respectively). Statistically significant increases in torsional rigidity, effective shear modulus, and effective shear stress were also found, as well as a 3.5 times increase in radiographic score (based on bone union). Histologic examination of the fracture callus indicated enhanced chondrogenesis at day 14 postfracture, with increased percent cartilage for the ZnCl2 /CaSO4 group compared with saline ( P = 0.0004) and CaSO4 ( P = 0.0453) controls. Long-term radiographic and histologic evaluation revealed no abnormal bone formation or infection up to 12 weeks postoperatively. Conclusions: The effective dose of ZnCl2 augmentation for the enhancement of fracture healing in rats was reduced 3-fold in this study compared with previous findings. Furthermore, CaSO4 acted synergistically with ZnCl2 to increase the mechanical strength and stability at the fracture site.